Respuesta :

Answer:

option C and D

Step-by-step explanation:

15x^2 - 46x + 35=0

First multiply 15  and 35. 15* 35 = 525

Product is 525  and sum is -46

-21 times  -25 = 525

-21 +(-25)= -46

break the middle term -46x using factors -21  and -25

[tex](15x^2 - 21x)+(-25x + 35)=0[/tex]

Take out GCf from each group

3x (5x-7) -5(5x-7)=0

Factor out 5x-7

(5x-7)(3x-5)=0

Now we set each factor =0 and solve for x

5x -7 =0  

add 7 on both sides and then divide it by 5

x= 7/5

3x -5 =0

add 5 on both sides and then divide by 3

x= 5/3